Paradigms for Sustainable Development: Implications of Management Theory - Dutta, Saurav; Lawson, R.; Marcinko, D. (Wiley Interscience, 2012)
We provide a framework for examining the trade-offs between socio-environmental, organizational, and managerial goals. Using this framework we examine management choices under agency and stewardship theories. We advance a theory of social stewardship to explain behavior inconsistent with both agency and stewardship. We illustrate that social stewardship behavior by managers and principals, while best from a societal perspective, is not a viable management approach under current business and regulatory conditions. This conclusion is vital to public policymakers who seek to foster socially desirable behavior by publicly traded companies. © 2011 John Wiley & Sons, Ltd and ERP Environment.